Virtual Conference: A Telecooperative Learning Environment - Kremer, H. Hugo (Proceedings of the International Conference on Networked Learning, 2004)
Virtual conferences are used as a special form of complex learning environment. Students, experts and interested people coming in a virtual environment together to work in cooperative decentralized structures. This concept gives students the opportunity to look beyond ‚the walls‘ of a traditional seminar in a university. With virtual conference we have a shift from guided learning to a kind of independent and experiential learning (see Simons 2001, p. 176). This concept gives students the opportunity to look in an active way beyond the ‘walls’ of a traditional seminar in a university. In an initial experiment, we tried out a virtual conference with the topic ‘e-Learning in vocational education’.